The analysis of tropical temperate trough-associated rainfall onsets and their influence on maize yields in the Maize Triangle, South Africa - Ndarana, Thando (University of Pretoria, 2024)
Dissertation (MSc (Environmental Management))--University of Pretoria, 2024.